A Generalized Scalar Pulse-width Modulation for Nine-switch Inverters - Bradaschia, Fabrício; Limongi, Leonardo R.; de Andrade, Felipe C.; Azevedo, Gustavo M. S. (Eletrônica de Potência, 2014)
The nine-switch inverter has been proposed recently and, since then, a large number of applications has been investigated, specially as a substitute to the dualbridge (back-to-back) converter. The main advantage of the nine-switch inverter is its lesser number of switches (nine instead of twelve of the back-to-back converter), which has as a tradeoff some restrictions in the total attainable amplitude at its outputs, dependent on the phase shift between its two terminal sets. Thus, when migrating modulation techniques from the conventional three-phase inverter to the nine-switch inverter, more concerns have to be addressed. This paper deals with pulse-width modulation strategies that can be easily implemented by using the concept of generalized scalar modulation in this type of inverter. In fact, such concept leads to a systematic and straight approach to the generation of any continuous or discontinuous pulsewidth modulation strategy. Aiming the reduction of switching losses, the generalized modulation is applied with a specific distribution parameter that reduces the number of switchings and the power losses of the three-phase nine-switch inverter. Experimental results confirm the validity of the proposed method.